Pengaruh Pola Asuh terhadap Kemampuan Komunikasi Siswa dalam Pembelajaran Matematika di Kelas III MI Gedanganak Kecamatan Ungaran Timur Kabupaten Semarang - Kurniyawati, Ana; Praptiningsih, Dra; Sri Legowo, Yogi Ageng (Faculty of Teacher Training and Education of Undaris, 2023)
This research was motivated by difficulties when conveying mathematical ideas and when working on essay questions, there were some students who just counted the numbers without knowing the meaning of the problem or without knowing the meaning of each step of solving the problem. The purpose of this study was to determine whether or not there was an influence of parenting on students' communication skills in learning mathematics in class III MI Gedanganak, East Ungaran District, Semarang Regency. The type of research used is quantitative research. The research subjects were class III students of MI Gedanganak, totaling 120 students with 30 samples. The variables of this study are parenting style and students' communication skills in learning mathematics. The data collection technique is using a questionnaire. Then the results of the data obtained were analyzed using arithmetic T test. Based on the results of the research and after the data was analyzed using the T-test, there was an influence of parenting style on students' communication skills in learning mathematics. This is indicated by the results of the calculated T-test which is greater than the T distribution table (2.750 > 2.042), which means that Ho is rejected and Ha is accepted. This means that there is an influence of parenting style and students' communication skills in learning mathematics.Keywords: parenting, parents, communication skills, students in learning Mathematics